2021
DOI: 10.1177/1403494821993711
|View full text |Cite
|
Sign up to set email alerts
|

Locked and lonely? A longitudinal assessment of loneliness before and during the COVID-19 pandemic in Norway

Abstract: Aims: There are concerns that lockdown measures taken during the current COVID-19 pandemic lead to a rise in loneliness, especially in vulnerable groups. We explore trends in loneliness before and during the pandemic and differences across population subgroups. Methods: Data were collected via online questionnaires in June 2020 and four to eight months prior in two Norwegian counties ( N=10,740; 54% women; age 19–92 years). Baseline data come from the Norwegian Counties Public Health Survey (participation rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
56
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 30 publications
10
56
1
6
Order By: Relevance
“…This is possibly because adolescents' relationships with peers and parents did not deteriorate during the pandemic. This nding is also in line with a longitudinal study among Norwegian adults that observed stable or even falling loneliness trends during the pandemic 36 .…”
Section: The Effect Of the Covid-19 Pandemic On Adolescentssupporting
confidence: 91%
“…This is possibly because adolescents' relationships with peers and parents did not deteriorate during the pandemic. This nding is also in line with a longitudinal study among Norwegian adults that observed stable or even falling loneliness trends during the pandemic 36 .…”
Section: The Effect Of the Covid-19 Pandemic On Adolescentssupporting
confidence: 91%
“…Studies have provided conflicting results concerning changes in the prevalence of loneliness during the COVID-19 pandemic. While some research has indicated that loneliness may have increased in the general population ( Killgore et al, 2020b ), other studies have reported that there has been no change in overall population loneliness in the pre- and pandemic period ( Hansen et al, 2021 ; Luchetti et al, 2020 ). It is uncertain what underlies these differences across studies and whether they relate to methodological factors such as the loneliness measures used, the different time periods examined/used for comparison, or differences in the COVID-19 situation in different countries and preventive measures implemented and/or the extent of their enforcement.…”
Section: Discussionmentioning
confidence: 99%
“…Are there signs of emotional fatigue or increasing loneliness as the pandemic drags on and returns for a second wave in Norway during the fall of 2020? On March 12, 2020, one day after the World Health Organization (WHO) declared COVID-19 a pandemic, the Norwegian government issued several restrictions, including closure of schools, nonessential businesses, and many public facilities (Hansen et al 2021 ; The Norwegian Government 2021 ). While the formal “lockdown” measures were relaxed or removed during the late spring and summer of 2020, the social distancing recommendations remained (e.g., maintain social distance and avoid social gatherings and public transportation).…”
Section: Introductionmentioning
confidence: 99%